Intercropping with Paris polyphylla and Ganoderma lucidum: regulatory effects on the rhizosphere microbial community and the quality of Polygonatum cyrtonema - Zheng, Huiyong; Zhu, Yanming; Liao, Penghui; Lin, Fengfang; Ye, Wei; Mao, Fanghua; Fang, Liang; Fang, Yanghui; Su, Hailan (Frontiers in Microbiology, 2025)
IntroductionOptimizing the cultivation of Polygonatum cyrtonema requires a comprehensive understanding of how intercropping influences both its quality and the rhizosphere microenvironment.MethodsThis study conducted a comparative analysis between monoculture cultivation of P. cyrtonema (PC) and two intercropping systems: P. cyrtonema with Paris polyphylla (PCPP) and with Ganoderma lucidum (PCG). The investigation assessed the influence of these cultivation systems on yield, quality attributes, soil physicochemical characteristics, and rhizosphere microbial communities.ResultsBoth intercropping systems significantly enhanced nutrient accumulation in the rhizosphere. Specifically, the PCG system increased available potassium by 72.76%, while the PCPP system elevated alkali-hydrolyzable nitrogen and total nitrogen by 7.19% and 7.02%, respectively, relative to PC. Additionally, both intercropping systems increased the relative abundance of microbial taxa such as Furcasterigmium and unclassified_f__Mortierellaceae. The PCPP system additionally promoted the proliferation of beneficial microorganisms, including Burkholderia-Caballeronia-Paraburkholderia, Rhodomicrobium, and norank_c_AD3. Available potassium and phosphorus were identified as key factors driving alterations in the rhizosphere microbial community structure. Although intercropping did not significantly affect P. cyrtonema yield, the PCPP system improved water-soluble extract content by 2.8% and polysaccharide content by 12.1% compared to monoculture.DiscussionThese findings indicate that intercropping modulates P. cyrtonema quality through synergistic interactions between soil nutrients and microbial community composition, with the PCPP system recommended as an optimal approach for integrated forest-based cultivation.